Soil mycobiomes in native European aspen forests and hybrid aspen plantations have a similar fungal richness but different compositions, mainly driven by edaphic and floristic factors - Rähn, Elisabeth; Lutter, Reimo; Riit, Taavi; Tullus, Tea; Tullus, Arvo; Tedersoo, Leho; Drenkhan, Rein; Tullus, Hardi (Frontiers in Microbiology, 2024)
The cultivation of short-rotation tree species on non-forest land is increasing due to the growing demand for woody biomass for the future bioeconomy and to mitigate climate change impacts. However, forest plantations are often seen as a trade-off between climate benefits and low biodiversity. The diversity and composition of soil fungal biota in plantations of hybrid aspen, one of the most planted tree species for short-rotation forestry in Northern Europe, are poorly studied. The goal of this study was to obtain baseline knowledge about the soil fungal biota and the edaphic, floristic and management factors that drive fungal richness and communities in 18-year-old hybrid aspen plantations on former agricultural soils and compare the fungal biota with those of European aspen stands on native forest land in a 130-year chronosequence. Sites were categorized as hybrid aspen (17-18-year-old) and native aspen stands of three age classes (8-29, 30-55 and 65-131-year-old). High-throughput sequencing was applied to soil samples to investigate fungal assemblages. Native aspen forests showed a higher ectomycorrhizal fungal richness than plantations, regardless of forest age. Short-distance type EcM genera dominated in both plantations and forests. The richness of saprotrophs was similar between forests and plantation and was highest in the middle-aged class native forest stands. The fungal communities of native forests and plantations were significantly different. Community composition varied more, and the natural forest sites were more diverse than the relatively homogeneous plantations. Soil pH was the best explanatory variable to describe soil fungal communities in hybrid aspen stands. Soil fungal community composition did not show any clear patterns between the age classes of native aspen forests. We conclude that edaphic factors are more important in describing fungal communities in both forests and plantations than forest thinning, age, or former land use for plantations. Although first-generation hybrid aspen plantations and native forests are similar in overall fungal diversity, their taxonomic and functional composition is strikingly different. Therefore, hybrid aspen plantations can be used to reduce felling pressure on native forests, however our knowledge is still insufficient to conclude that plantations could replace native aspen forests from the soil biodiversity perspective.